ANALISIS SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI PADA PROYEK PRESERVASI JALAN BTS. ACEH TENGAH/NAGAN RAYA–LHOK SEUMOT–JEURAM - Firdausi Nuzula; Sofyan M Saleh; Yusria Darma (Prodi Magister Teknik Sipil Unsyiah, 2023)
Based on the number of work accidents in the construction industry sector that get a relatively high percentage, it is necessary to identify the application of SMKK through the research